Exposure to xenoestrogens alters the expression of key morphoregulatory proteins of oviduct adenogenesis in the broad-snouted caiman (Caiman latirostris) - Tavalieri, Yamil Ezequiel (2021)
Endocrine disrupting compounds (EDCs) are contaminants ubiquitously found in the environment, which pose a potential threat to aquatic and wetland ecosystems. Caiman latirostris, a crocodilian species that inhabits South American wetlands, is highly sensitive to EDC exposure. Previously, we reported that early postnatal exposure to EDCs such as Bisphenol A (BPA) and 17β-Estradiol (E2) alters C. latirostris oviduct differentiation. The aim of this work was to elucidate the molecular mechanisms behind this alteration. To accomplish this, we established the ontogenic changes in histological features and the expression of Wnt-7a, Wnt-5a, β-catenin, FoxA2, desmin, and alpha smooth muscle actin (α-SMA) in the oviduct of C. latirostris. Then, we evaluated the effects of BPA and E2 exposure on these histological features and protein expressions. Our results showed that during the postnatal differentiation of the oviduct the presence of histological features related to adenogenesis is associated with the levels of expression of FoxA2, β-catenin, Wnt-5a and Wnt-7a. Early postnatal exposure to BPA and E2 decreased the presence of histological features related to adenogenesis and altered the levels of expression of FoxA2, β-catenin, Wnt-5a and Wnt-7a, as well as the desmin/α-SMA ratio. These findings suggest that altered levels of Wnt-7a, Wnt-5a, β-catenin and FoxA2 could play a role in the BPA and E2–induced alteration in oviduct differentiation in C. latirostris. Thus, impaired adenogenesis and, probably, impaired reproduction in wildlife naturally exposed to BPA and other estrogenic agonists cannot be completely ruled out.